Integrated weed management and weed species diversity - Clements, D.R.; Weise, S.F.; Swanton, C.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
Alternative practices for weed management, such as integrated weed management (IWM) may allow the persistence of weed populations below a given economic threshold. Increased species diversity of weeds also may result. If diversity increases, and the number of ecological interactions also increases, weed species should be viewed as an interactive community, rather than an unrelated set of targets for control. In this review we summarize how diversity is evaluated in unmanaged Systems, examine how IWM techniques may alter the diversity of weed species and suggest how strategies can be developed for managing weed diversity under IWM. Methods used to evaluate diversity in natural Systems may be used to evaluate weed diversity in alternative Systems of weed management. We made preliminary calculations of diversity for reduced tillage, modified herbicide use, crop rotation, critical period of weed control, techniques to improve crop competitiveness, and alternative control methods. Many of these IWM techniques potentially may result in changes in weed species diversity. We examined potential effects of these changes in weed diversity within six primary elements of community ecology: colonization, disturbance, the physical environment, interactions with other communities, community interactions and community dynamics. Opportunities to develop strategies of community management exist within each of these elements. If diversity could be managed while maintaining acceptable crop yields, some previously unrealized benefits of the presence of weeds could be seen, as predicted by relationships among plants of unmanaged communities. Moreover, the goal of producing a more sustainable System that incorporates the diversity of the weed community would be complemented by trends in policy towards encouraging biodiversity in agroecosystems.